Can the combination of proanthocyanidin and vitamin E or palm oil effectively protect enamel against in vitro erosive and abrasive challenges? - Daiana da Silva MARTINS; Ana Paula BOTEON; Amanda Moura FERREIRA; Ana Luiza Bogaz DEBORTOLLI; Isabella Claro GRIZZO; Franciny Querobim IONTA; Thiago Saads CARVALHO; Marilia Afonso Rabelo BUZALAF; Daniela RIOS; Heitor Marques HONÓRIO (University of São Paulo, 2024)
Abstract Objectives This study aimed to assess the effect of proanthocyanidin, palm oil and vitamin E against erosive and erosive+abrasive challenges in vitro after enamel pellicle formation in situ. Methodology Bovine enamel blocks (n=84) were obtained and divided into the following treatment groups: negative control (NC) - deionized water; positive control (PC) - SnCl2/NaF/AmF-containing solution; palm oil (PO); 2% proanthocyanidin (P2); vitamin E (VitE); 2% proanthocyanidin+palm oil (P2PO); and 2% proanthocyanidin+vitamin E (P2VitE). For 5 days, one half of the sample from each group was subjected to erosion and the other half was subjected to erosion+abrasion. The acquired enamel pellicle (AEP) was pre-formed in situ for 30 minutes. The specimens were then treated in vitro with solutions (500 µl, 30s for each group). Subsequently, the blocks were left in the oral cavity for another hour to obtain the modified AEP. The blocks were immersed in 0.5% citric acid (pH=2.5) for 90s, 4×/day. AEP formation and treatment were carried out before the first and third erosive challenges, and after these challenges, abrasive cycles (15s) were performed on half of the samples. Enamel wear was quantified by profilometry and data were analyzed by two-way ANOVA and Tukey's test (p<0.05). Results All groups showed higher wear when exposed to erosion+abrasion than when exposed to erosion alone (p=0.0001). PO, P2VitE, P2, and P2PO showed enamel wear similar to the PC group, but only PC, PO and P2VitE differed from the NC group. The other groups behaved similarly to NC. Conclusion It was concluded that the combination of proanthocyanidin and vitamin E was effective in reducing wear in the face of in vitro erosive and erosive+abrasive challenges.